Study Neutronic of Small Pb-Bi Cooled Non-Refuelling Nuclear Power Plant Reactor (SPINNOR) with Hexagonal Geometry Calculation - Dwita Nur Krisna; Zaki Su'ud (Institut Teknologi Bandung, 2012)
Nuclear reactor technology is growing rapidly, especially in developing Nuclear Power Plant (NPP). The utilization of nuclear energy in power generation systems has been progressing phase of the first generation to the fourth generation. This final project paper discusses the analysis neutronic one-cooled fast reactor type Pb-Bi is capable of operating up to 20 years without refueling. This reactor use Uranium Nitride Thorium as fuel and operating on power range 100– 500MWtNPPs. The method of calculation used a computer simulation program utilizing the SRAC. SPINNOR reactor design is designed with the geometry of hexagonal shaped terrace that radially divided into three regions, namely the outermost regions with highest percentage of fuel, the middle regions with medium percentage of fuel, and most in the area with the lowest percentage. SPINNOR fast reactor operated for 20 years with variations in the percentage of uranium-233 by 7%, 7.75% and 8.5%. Neutronik the calculation and analysis show that the design can be optimized in a fast reactor for thermal power output SPINNOR 300MWt with a fuel fraction 60% and variations of Uranium-233 enrichment of 7% - 8.5%